Identifying Surface Changes on HRSC Images of the Mars South Polar Residual Cap (SPRC) - Putri, ARD; Sidiropoulos, P; Muller, J-P (International Society for Photogrammetry and Remote Sensing (ISPRS), 2016)
The surface of Mars has been an object of interest for planetary research since the launch of Mariner 4 in 1964. Since then different cameras such as the Viking Visual Imaging Subsystem (VIS), Mars Global Surveyor (MGS) Mars Orbiter Camera (MOC), and Mars Reconnaissance Orbiter (MRO) Context Camera (CTX) and High Resolution Imaging Science Experiment (HiRISE) have been imaging its surface at ever higher resolution. The High Resolution Stereo Camera (HRSC) on board of the European Space Agency (ESA) Mars Express, has been imaging the Martian surface, since 25th December 2003 until the present-day. HRSC has covered 100% of the surface of Mars, about 70% of the surface with panchromatic images at 10-20 m/pixel, and about 98% at better than 100 m/pixel (Neukum et. al., 2004), including the polar regions of Mars. The Mars polar regions have been studied intensively recently by analysing images taken by the Mars Express and MRO missions (Plaut et al., 2007). The South Polar Residual Cap (SPRC) does not change very much in volume overall but there are numerous examples of dynamic phenomena associated with seasonal changes in the atmosphere. In particular, we can examine the time variation of layers of solid carbon dioxide and water ice with dust deposition (Bibring, 2004), spider-like channels (Piqueux et al., 2003) and so-called Swiss Cheese Terrain (Titus et al., 2004). Because of seasonal changes each Martian year, due to the sublimation and deposition of water and CO2 ice on the Martian south polar region, clearly identifiable surface changes occur in otherwise permanently icy region. In this research, good quality HRSC images of the Mars South Polar region are processed based on previous identification as the optimal coverage of clear surfaces (Campbell et al., 2015). HRSC images of the Martian South Pole are categorized in terms of quality, time, and location to find overlapping areas, processed into high quality Digital Terrain Models (DTMs) and Orthorectified Images (ORIs) and projected into polar stereographic ...